Construction system of Masjid Jamek Sultan Abdul Samad - Kamarul Bahrin, Akmal Arif; T. Noorshahrani, Hilman Idris; Abdul Rahim, Asiah; Nordin, Nasrullah; Asif, Nayeem; Alnahdi, Salman Saleh Ali; Md Tamizi, Nurul Izzanie; Mohamad Yusuf, Fatin Nabilah (KAED Universal Design Unit (KUDU), 2022)
This chapter will be focused on the construction of Masjid Jamek Sultan Abdul Samad. The construction of Masjid Jamek Sultan Abdul Samad was based on materials and construction from colonials which were newly introduced to Malaysia at that time. These chapter will go through the types of construction, structural and non-structural system as well as other features in the Masjid Jamek Sultan Abdul Samad